Electrophoretic deposition of Li4Ti5O12 nanoparticles with a novel additive for Li-ion microbatteries1. Issue 76 (19th August 2015) - Kyeremateng, Nana Amponsah; Dinh, Ty Mai; Pech, David
<x xml:space="preserve">Abstract</x> This work underscores electrophoretic deposition as a suitable alternative to prepare self-supported micro- or nano-structured Li4Ti5O12 for 3D Li-ion microbatteries.